2014
DOI: 10.1007/s00167-014-3052-z
|View full text |Cite|
|
Sign up to set email alerts
|

Bankart repair versus Bankart repair plus remplissage: an in vitro biomechanical comparative study

Abstract: In cadaveric shoulders with combined Bankart and Hill-Sachs lesions, Bankart lesion repair associated with remplissage restored intact joint stiffness contrary to Bankart lesion repair alone. This increase in stiffness was associated with a decrease in external rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 38 publications
2
18
0
1
Order By: Relevance
“…Restriction of ROM represents a shortcoming of remplissage, as described in many reports, and it results from the fact that remplissage is a technique of non-anatomical repair whereby the Hill-Sachs lesion is filled by advancing the posterior articular capsule and the infraspinatus muscle tendon; the new footprint is located closer to the posterior articular cavity edge, which can cause ROM restriction (particularly restriction of external rotation). The biomechanical study of Grimberg et al found that patients who underwent remplissage showed an 11.7° restriction of external rotation ROM, which differed significantly from that noted in patients who underwent Bankart repair alone [ 21 ]. Zhu et al reported an average improvement in flexion by 8° and restriction of external rotation by 1.9°, but these differences were not statistically significant [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Restriction of ROM represents a shortcoming of remplissage, as described in many reports, and it results from the fact that remplissage is a technique of non-anatomical repair whereby the Hill-Sachs lesion is filled by advancing the posterior articular capsule and the infraspinatus muscle tendon; the new footprint is located closer to the posterior articular cavity edge, which can cause ROM restriction (particularly restriction of external rotation). The biomechanical study of Grimberg et al found that patients who underwent remplissage showed an 11.7° restriction of external rotation ROM, which differed significantly from that noted in patients who underwent Bankart repair alone [ 21 ]. Zhu et al reported an average improvement in flexion by 8° and restriction of external rotation by 1.9°, but these differences were not statistically significant [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their 2000 article, Burkhart and De Beer 3 reported that arthroscopic Bankart repair patients with bony defects were at a greater risk of recurrent dislocation. This has been echoed in subsequent studies 20, 21, 22, 23, 24. Currently, arthroscopic Bankart repair and the open Latarjet procedure are the preferred surgical techniques when addressing recurrent shoulder dislocation.…”
Section: Discussionmentioning
confidence: 95%
“…Biomechanical studies on cadavers have reported loss of external rotation, including Grimberg et al, 19 who found a 11.7 loss in external rotation after Bankart plus remplissage compared with the intact cadaveric specimen; however, their Bankart plus remplissage restored stiffness equal to the intact model unlike Bankart repair alone in cadavers with concurrent Bankart and Hill-Sachs defects. The same results of improved stiffness and stability with loss of external rotation in the cadaveric model were found by Giles et al 20 and Elkinson et al 21 The clinical studies measuring range of motion, however, have not demonstrated this to be a significant problem.…”
Section: Discussionmentioning
confidence: 99%